EVALUASI REPRODUKSI INDUK SAPI POTONG LIMOSIN DENGAN SISTEM PERKAWINAN INSEMINASI BUATAN (STUDI LAPANG DI KELURAHAN KLAMPOK KECAMATAN SANANWETAN KOTA BLITAR - Muhammad Hamzah; Nita opi ari kustanti; Risma Novela Esti (Universitas Islam Balitar, 2020)
The aim of this study was to determine reproductive evaluation of Limosin beef cattle by using artificial insemination mating systems located in Klampok Village, Sananwetan District, Blitar City. The results of the study, mean service value per conception (SC) which has a result of 1.55. The mean conception rate (CR) score was 55.5%. The average value of Days Open (DO) has a yield of 123.5 days. The mean value of the Calving Interval (CI) is 372.5 days. The conclusion of this study is the evaluation of the reproduction of Limosin beef cattle using the artificial insemination mating system in Klampok Village, Sananwetan District, Blitar City produces good values ​​including the Value of Service per Conception (S / C), Days Open (DO), Clving Interval (CI) while Conception speed value is still low below the average range.